Effectiveness of Dual Space Inquiry Based E-Module on Student Learning Outcomes and Motivation in Work and Energy Material - Zahara Rahmadhani; Fuja Novitra; Yenni Darvina; Emiliannur Emiliannur (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Physics learning should enable students to achieve strong conceptual understanding and high learning outcomes while remaining actively motivated throughout the learning process. However, learning outcomes and learning motivation in physics remain challenging, particularly in the topic of work and energy, where students often experience difficulties in understanding concepts and actively engaging in learning. Preliminary study findings indicated that students' physics learning outcomes remained low, with a mastery rate of only 22%. Student learning motivation was also suboptimal, as evidenced by low percentages across several motivation indicators. To address these issues, a Dual Space Inquiry-based e-module was implemented as an interactive digital learning resource. This study aimed to examine the effectiveness of the Dual Space Inquiry-based e-module in improving students' learning outcomes and motivation. A pre-experimental method with a one-group pretest-posttest design was employed. The sample consisted of 30 students from class X.E1, selected using purposive sampling. Data were collected via learning outcome tests and learning motivation questionnaires. Results showed that the average learning outcome score increased from 49.67 to 80.50, with an N-Gain of 0.59 (medium category) and an effect size of 1.61. Learning motivation increased from 67.27 to 81.47, with an N-Gain of 0.43 (medium category) and an effect size of 2.391. Paired sample t-test results yielded a significance value of <0.05. Thus, the Dual Space Inquiry-based e-module is effective in enhancing students' learning outcomes and motivation and serves as an alternative digital teaching material for physics instruction.